Consolidated Feedback on Tanzania Higher Education University Strategic Investment Plans - Adam, Taskeen; Koomar, Saalim; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk Response provides feedback on 15 Tanzania University Strategic Implementation Plans (USIPs) submitted to the Word Bank’s Higher Education for Economic Transformation Project (HEET). The feedback is intended to enhance and strengthen the plans provided by universities such that the US$300 million is allocated and spent most effectively.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3986727 2129771:B5Z854HJ 2339240:IEATEWRY 2405685:7AFXFRPC
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence; dode_eth-src-eth; dode_eth-trf2-dode